2007
DOI: 10.1002/hbm.20492
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ageing on complex brain networks: A graph theoretical analysis

Abstract: Objective: To determine the functional connectivity of different EEG bands at the ''baseline'' situation (rest) and during mathematical thinking in children and young adults to study the maturation effect on brain networks at rest and during a cognitive task. Methods: Twenty children (8-12 years) and twenty students (21-26 years) were studied. The synchronization likelihood was used to evaluate the interregional synchronization of different EEG frequency bands in children and adults, at rest and during math. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 42 publications
5
96
1
Order By: Relevance
“…The finding that small-worldness and cost efficiency were reduced in seniors is in agreement with previous results for resting state networks (Achard et al, 2007;Micheloyannis et al, 2009). We can thus generalize the result to working memory networks.…”
Section: Matthä Us Et Alsupporting
confidence: 92%
“…The finding that small-worldness and cost efficiency were reduced in seniors is in agreement with previous results for resting state networks (Achard et al, 2007;Micheloyannis et al, 2009). We can thus generalize the result to working memory networks.…”
Section: Matthä Us Et Alsupporting
confidence: 92%
“…In a study of language perception, agerelated declines in global efficiency were found [52] . During mathematical thinking, the α2 band showed a degree of SWN disorganization in adults compared to children, whereas β and γ bands showed lower synchronization and lower SWN organization [53] . Recently published reviews are helpful to understand the normal organization and development [54][55][56][57][58] .…”
Section: Normal Brain Network Organizationmentioning
confidence: 91%
“…The topological cost efficiency (Latora and Marchiori, 2001) of brain functional networks oscillating at ␤-band frequencies was shown to be more strongly correlated with variability of performance on a working memory task than the cost efficiency of networks operating at other frequencies (Bassett et al, 2009). Working memory task-related changes in synchronization likelihood and smallworldness of MEG networks were most salient in ␤-and ␥-bands (Micheloyannis et al, 2009). Together, it seems that ␤-band synchronization is very likely a key mechanism in the task-related workspace configuration of large-scale brain functional networks.…”
Section: Complex Network and Workpace Theorymentioning
confidence: 95%